Permohonan Penundaan Kewajiban Pembayaran Utang (PKPU) pada Masa Pandemi Covid-19 (Putusan Nomor 110/Pdt. Sus- PKPU/2020/Pn Niaga. Jkt. Pst) - Misrany Anggita Br Haloho (Polyscopia, 2024)
This research aims to analyze the peace mechanism within the context of settlement through PKPU, focusing on Decision Number 110/Pdt. Sus- PKPU/2020/PN Niaga. Jkt. Pst. Employing a normative approach, it conducts legal case studies to examine behavioral norms in society. Findings indicate that PKPU offers a viable solution for debtor-creditor disputes amid the Covid-19 pandemic, providing entrepreneurs with survival options. Debtors are granted the opportunity to defer payment obligations to all creditors, mitigating potential conflicts. The judge's decision in case 10/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst was deemed appropriate, with PT. Duta Pramindo Sejahtera's peace proposal garnering approval from over two-thirds of creditors. This approval, based on the proposed obligation settlement plan, assures creditors of legal certainty and safeguards against deceit while still offering debtors the chance to restructure their businesses.